2021
DOI: 10.1038/s41467-021-23357-9
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric nanohole array metasurface for high-resolution near-field sensing and imaging

Abstract: Dielectric metasurfaces support resonances that are widely explored both for far-field wavefront shaping and for near-field sensing and imaging. Their design explores the interplay between localised and extended resonances, with a typical trade-off between Q-factor and light localisation; high Q-factors are desirable for refractive index sensing while localisation is desirable for imaging resolution. Here, we show that a dielectric metasurface consisting of a nanohole array in amorphous silicon provides a favo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 46 publications
0
99
0
Order By: Relevance
“…This allows having a large area but still exploiting the advantages of near-field optics, in particular in terms of strong resolution. This approach has been experimentally validated in the literature with simple and feasible systems [42]. This behavior is also useful to obtain additional information about the first stage of the bacteria infection, when the bacteria cells enrich before they start to interact with each other to form the biofilm.…”
Section: Dual Array Of Interdigitated Electrodes: Architecture and Operationmentioning
confidence: 97%
See 1 more Smart Citation
“…This allows having a large area but still exploiting the advantages of near-field optics, in particular in terms of strong resolution. This approach has been experimentally validated in the literature with simple and feasible systems [42]. This behavior is also useful to obtain additional information about the first stage of the bacteria infection, when the bacteria cells enrich before they start to interact with each other to form the biofilm.…”
Section: Dual Array Of Interdigitated Electrodes: Architecture and Operationmentioning
confidence: 97%
“…Under this condition, the monitoring of the chemical and biological The structure exploiting the GMR effect has been designed to obtain a resonance condition for λ > 800 nm, where the absorption losses of silicon decrease [41], with the aim of achieving a higher extinction ratio and higher Q-factor, together with a strong energy confinement close to the surface to enhance the light interaction with the bacteria. The strong refractive index contrast between silicon and the surrounding medium allows a high confinement of the electromagnetic field at the sensor surface, enabling the use of the INEs section for hyperspectral imaging technique, as described in detail in [42], which allows the refractive index imaging, thus localizing objects on the grating by detecting the spatial resonance distribution. An inverted microscope configuration can be used to characterize the sensor, with the light source illuminating from the top and the reflected signal collected from the same side of the setup by a conventional CMOS camera.…”
Section: Dual Array Of Interdigitated Electrodes: Architecture and Operationmentioning
confidence: 99%
“…More recently, Conteduca et al demonstrated a dielectric nanohole array (Figure 4c) in amorphous silicon (a:Si) that supports two optical modes, both with relatively moderate Q-factors (300-400) and submicron spatial resolution, desirable for both imaging and biochemical sensing [68]. They demonstrated IgG sensing with a limit of detection (LOD) lower than 1 pg/mL using a TM mode with high Q-factor and high surface sensitivity, while the high resonance amplitude and strong confinement of the TE mode enables a spatial resolution below 1 μm that clearly resolves features of individual E. coli bacteria (Figure 4d).…”
Section: Metamaterial-enhanced Refractometric Microscopymentioning
confidence: 99%
“…Fano resonances brought by symmetry-breaking structures like nanocubes on substrate [12], gold nano-disks integrated with indium tin oxide (ITO) [22], plasmonic nanoantenna on a graphene sheet [23], nanodisk surrounded by gold nanorods with different orientations [24], etc. often has high sensitivity to surrounding environment [25][26][27]. LSPR brought by different metal nanostructures i.e., nanoparticles [28], nanorods [29], nanostars [30] is also utilized in optical sensing for its ability of wavelength shift with the change of the surrounding [31] and enhancing scattering [32].…”
Section: Introductionmentioning
confidence: 99%